Role of the Kazakhstan-German Cooperation in Improving Scientific Tools for Evaluation of Vocational Education Programs - S. G. Karstina; O. N. Zechiel; C. Machado (Высшее образование в России, 2021)
The work carried out within the framework of the German-Kazakh project “GeKaVoс – Transfer of dual training in logistics, mechatronics and sustainable energy supply to Kazakhstan” can be considered as one of the crucial aspects of the contribution to improving the quality of system of technical and vocational education (TVET), the achievement of high rates of employment of graduates of the TVET system, improve the ratio of supply and demand in the labor market.As the analysis of the TVET system in Kazakhstan presented in the article shows, different forms of cooperation between participants of the educational process in the country (corporate partnership, industrial clusters, patronage of large and medium-sized enterprises over educational institutions, etc.) contribute to the development of a market-oriented education system. Monitoring and evaluation of the effectiveness of technical and vocational education, as well as identifying opportunities to improve its quality and scope require understanding of its nature, its functions, goals and key characteristics, the application of effective scientific tools to assess vocational technical education and training of trainers (tutors) (TVET).The paper shows that the success of the transfer of educational programs depends primarily on the willingness to work together of all the stakeholders, the creation of systematic structures of interaction in the development of educational programs of different levels, improving methods of forecasting demand not only for certain professions, but also for professional and pre-professional competencies. The purpose of scientific evaluation of the dual system and workplace training is to prove its effectiveness as an educational strategy that provides students with real work experience, where they can apply social and technical skills and develop them.